EDUCATIONAL TRANSFORMATION THROUGH GOOD UNIVERSITY GOVERNANCE: HR EMPOWERMENT STRATEGIES IN PRIVATE UNIVERSITIES - Ashari, Chriestine Ayu (UTSAHA: Journal of Entrepreneurship, 2024)
Private universities in Indonesia have a crucial role in facilitating students' access to higher education. However, many private universities still struggle with difficulties, such as inadequate quality and non-optimal management. Therefore, educational transformation is needed through the improvement of good university governance. Good governance requires strong leadership, strategic planning, healthy financial management, and effective supervision. In addition, the empowerment of human resources, such as lecturers and education personnel, is also crucial to improve the quality of graduates and the competitiveness of private universities. Thus, they are expected to produce graduates who are competent and ready to meet global challenges, and contribute to national development. This research aims to examine and analyze the role of Good University Governance (GUG) in empowering Human Resources (HR) in private universities. This research method used qualitative methods to determine the implementation of GUG in improving the performance and capacity of human resources in universities. Data analysis was conducted to understand the impact of GUG on various aspects of HR empowerment, such as professional development, work motivation, and involvement in decision-making. The results showed that the implementation of GUG in private universities has contributed significantly to improving the quality of human resources. Transparency and accountability in university management encourage active participation of lecturers and staff, while continuous professional development policies improve their competence and performance. In addition, participation in decision-making creates a more inclusive and collaborative work environment, which further supports innovation and creativity.